Utilization of Hotspot Network Bandwidth Management at SMK Muhammadiyah Parkan - Zihan Fauziah Rahmah; Mahbubul Wathoni; Yasin Efendi (Yayasan Adra Karima Hubbi, 2023)
Mikrotik is a routing activity using Wireless Local Area Network (W-LAN) technology. Mikrotik is an operating system and software used to function a computer as a router. The model used in this study refers to the PPDIOO type development model with 6 stages, namely Prepare, Plan, Design, Implement, Operate, and Optimize. Validity tests and effectiveness tests include the product being able to run optimally and successfully improving the quality of existing network bandwidth. Data collection instruments used interviews and observation. Data collection was carried out in November 2022 at Muhammadiyah Parakan Vocational School. The results of the material expert validity test were 92%, the media expert validity test was 80%, the teacher response effectiveness test was 80% and the student effectiveness test was 88%